2004
DOI: 10.1016/j.jacc.2003.10.067
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of cardiopulmonary functional improvement after transcatheter atrial septal defect closure in asymptomatic adults

Abstract: Transcatheter ASD closure leads to a significant improvement in cardiopulmonary function within six months, via an increase in peak oxygen pulse. An increase in both left ventricular stroke volume and cardiac output due to a positive ventricular interaction is the mechanism leading to improved peak Vo(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
103
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(115 citation statements)
references
References 15 publications
10
103
1
Order By: Relevance
“…34,35 Thus, it has been demonstrated that torsional deformation is a sensitive indicator of LV function. Global LV systolic function has been shown to be impaired in ASD [8][9][10]36,37 and we also found that the LVEF in patients with ASD was lower than that of normal controls. Moreover, our results showed that a lower EF in patients with ASD was associated with reduced LV torsion values.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…34,35 Thus, it has been demonstrated that torsional deformation is a sensitive indicator of LV function. Global LV systolic function has been shown to be impaired in ASD [8][9][10]36,37 and we also found that the LVEF in patients with ASD was lower than that of normal controls. Moreover, our results showed that a lower EF in patients with ASD was associated with reduced LV torsion values.…”
Section: Discussionsupporting
confidence: 66%
“…[1][2][3][4][5][6][7] Previous studies have demonstrated that right ventricular (RV) volume overload is associated with adverse left ventricular (LV) function in patients with ASD. [8][9][10] Recently, assessment of LV rotation has become an important approach for quantifying LV function. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] However, to the best of our knowledge there are no data available to date on the impact of RV volume overload on LV twist in patients with ASD.…”
mentioning
confidence: 99%
“…Recent additions to the literature have shown that, in younger adults, ASD closure leads to increased left ventricle diastolic diameter and overall function by 6 months [12].…”
Section: Limitationsmentioning
confidence: 99%
“…[3][4][5][6][7][8] In addition, functional capacity can improve significantly after closure. [9][10][11] For this reason, the American College of Cardiology/American Heart Association 2008 Guidelines for the Management of Adults With Congenital Heart Disease recommend device closure of secundum ASDs in the presence of right heart volume load, evidence of complications such as paradoxical embolism or orthodeoxiaplatypnea, and in the absence of pulmonary hypertension. 12 Similarly, the 2010 European Society of Cardiology Guidelines recommend closure in cases of significant shunt or after paradoxical embolism.…”
mentioning
confidence: 99%